Chemo-preventive activities of common vegetables' volatile organic compounds (VOCs) - Olusegun, Lasekan (Omics Publishing Group, 2014)
In the last few years, many research reports on the chemo-preventive activities of vegetables have been published. Vegetables are not only nutrient-dense food source but they are also rich in volatile organic compounds with known bioactivities beneficial to human health. A review of vegetables volatile constituents and their bioactivities is therefore important. It will display an overview and information regarding their role in the improvement of human health. The current status of research on volatile organic compounds in common vegetables and their potential roles in the prevention of various diseases associated with oxidative stress, such as cardiovascular and neurodegenerative diseases are reviewed. The major volatile compounds with roles in cardiovascular and neurodegenerative disease prevention are benzene propane nitrile commonly found in (Broccoli raab), hydroxycinnamates (lettuce), xanthorrihzol (artichoke), dially sulfide (onion and garlic), allicin (onion and garlic), and anthraquinone (rhubarb). The anti-microbial, anti-oxidant, and anti-thrombotic activities of other compounds such as trans-ocimene, β-selinene, fenchone, carotol, and others are also reported.